Prognostic value of serum alpha-fetoprotein in fulminant hepatic failure including patients treated by charcoal haemoperfusion. - Murray-Lyon, I M (1976)
Serum alpha-fetoprotein (AFP) levels have been measured sequentially by a radio-immunoassay method in 64 patients with fulminant hepatic failure. In 15 of the 64 patients (23%) AFP levels were raised but in only two did they exceed 500 ng/ml. Of the 23 survivors 11 (48%) had raised AFP levels compared with four of the 41 (9-8%) fatal cases (P less than 0-005). This rise in AFP levels was found early after the development of grade IV coma and constitutes an encouraging prognostic sign at a time when the liver function tests and EEG are unhelpful. A radioimmunoassay must be used if these small but significant rises in plasma concentration are to be detected. Twelve patients survived without showing a rise in plasma AFP at anytime during the illness. The four fatal cases who had raised AFP levels all had serious complications of fulminant hepatic failure. Charcoal haemoperfusion did not seem to increase the survival of AFP negative patients.